2017
DOI: 10.1021/acs.jpcc.7b01721
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Diffusing on Highly Curved Water–Oil Interface Using Three-Dimensional Single Particle Tracking

Abstract: Diffusion on highly curved surfaces is important to many industrial and biological processes. Despite the progress made in theoretical studies, how diffusion is affected by the curvature is unclear due to experimental challenges. Here, we measured the trajectories of polystyrene nanoparticles diffusing on highly curved water-silicone oil interface, where the oil droplet diameter ranges from several μm to as small as ∼400 nm. To analyze the diffusion coefficients on curved surface, an analytical solution develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…For example, it was shown that such particles took untenably long to reach equilibrium after adsorption to a liquid interface. 14 , 15 Furthermore, the translational and rotational diffusions of adsorbed particles were often found to be slower than the predictions of the Stokes–Einstein relation and hydrodynamic theories, 16 25 whereas the underlying mechanisms were not captured by the simulations. 26 , 27 Some reasons for the slow diffusion of micron-sized particles have been suggested such as the ubiquitous surface “defects” that induce multiple metastable pinning of the three-phase contact line, 28 30 producing an extra reverse random force to slow diffusion.…”
mentioning
confidence: 98%
“…For example, it was shown that such particles took untenably long to reach equilibrium after adsorption to a liquid interface. 14 , 15 Furthermore, the translational and rotational diffusions of adsorbed particles were often found to be slower than the predictions of the Stokes–Einstein relation and hydrodynamic theories, 16 25 whereas the underlying mechanisms were not captured by the simulations. 26 , 27 Some reasons for the slow diffusion of micron-sized particles have been suggested such as the ubiquitous surface “defects” that induce multiple metastable pinning of the three-phase contact line, 28 30 producing an extra reverse random force to slow diffusion.…”
mentioning
confidence: 98%
“…Visualizing the contact dynamics of micro-and nanodroplets is difficult. 39 Previously, our group has developed methods using electrogenerated chemiluminescence to visualize phase boundaries for large (10 s of μm) droplets. 28 The wetting of micro-and nanodroplets onto various hydrophilic and hydrophobic substrates will be the topic of future investigation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The aforementioned ideas and proposals to elucidate the particle transport in non-Euclidean spaces have been partially and recently corroborated in experiments of polystyrene nanoparticles diffusing on highly curved water-silicone oil interfaces [128]. However, further experimental and computational studies are needed in order to better understand the rich diffusion mechanisms that emerge in colloidal dispersions when the curvature plays an important role.…”
Section: Colloidal Soft Matter Physics and Geometrymentioning
confidence: 94%